The adoption of the sail in the Early Bronze Age Aegean (ca. 2550-2200 BC) and its impact on later Minoan, Aeginetan, and Mycenaean seafaring - Van de Moortel, Aleydis (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
This paper redates the adoption of the sail in the Aegean to ca. 2550‒2200 BC – significantly earlier than previously thought. It argues that the sail was introduced first in the East Aegean and from there in the Central and West Aegean, reaching Minoan Crete only ca. 1900 BC. Sailing technology seems to have come from Egypt via the Levant to the Aegean in the context of the Early Bronze Age Anatolian Trade Network. This new maritime technology had a major impact on the Aegean in the Middle and Late Bronze Ages, facilitating the rise of Aeginetan, Minoan, and Mycenaean maritime trade networks.